2011
DOI: 10.1177/0272431611426145
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety and Adolescents’ Friendships

Abstract: Research indicates social anxiety is associated with lower friendship quality, but little is known about the underlying mechanisms. This 2-month longitudinal study examined social withdrawal as a mediator of the social anxiety-friendship quality link in a sample of 214 adolescents (M age = 13.1 years, SD = .73) that included an oversampling of adolescents recently relocated to the community (n = 155). Findings provided preliminary support for the hypothesized models, in which social anxiety is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 47 publications
9
54
0
4
Order By: Relevance
“…In fact, students reporting high levels of general anxiety also report poor teacher and peer relationships as well as poor health (Erwin, ; Gaspar de Matos, Barrett, Dadds, & Shortt, ; Grills & Ollendick, ; Suhr‐Dachs, ). These findings are in line with studies from Pekrun () and Biggs and colleagues (), indicating that test‐anxious students are more likely to report high levels of social exclusion and perceived competition within the class context. Furthermore, personality aspects have shown to predict the number of peer relationships and conflict with peers (Asendorpf & Wilpers, ).…”
Section: Social Relationships In the School Contextsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, students reporting high levels of general anxiety also report poor teacher and peer relationships as well as poor health (Erwin, ; Gaspar de Matos, Barrett, Dadds, & Shortt, ; Grills & Ollendick, ; Suhr‐Dachs, ). These findings are in line with studies from Pekrun () and Biggs and colleagues (), indicating that test‐anxious students are more likely to report high levels of social exclusion and perceived competition within the class context. Furthermore, personality aspects have shown to predict the number of peer relationships and conflict with peers (Asendorpf & Wilpers, ).…”
Section: Social Relationships In the School Contextsupporting
confidence: 91%
“…The current study also found that positive peer relationships are associated with reduced levels of general anxiety, which supports previous research in the area (Biggs, Nelson, & Sampilo, ; Erwin, ; Flanagan et al., ; Gaspar de Matos et al., ; Grills & Ollendick, ). Being socially connected with a group mitigates the effects of stressful situations, such as having to take a test (Cohen & Wills, ; Lee & Robbins, ) and fosters healthy socio‐emotional development (Biggs et al., ; Osterman, ). With regard to test anxiety in particular, high levels of test anxiety have been shown to be related to poor peer relationships (Pekrun, ; Suhr‐Dachs, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further research into the mechanisms underlying the association of anxiety and depression with peer relations would help identify processes and skills to target in treatment. For example, social withdrawal has been found to mediate the association of social anxiety with low peer acceptance (Erath et al, 2007) and with low friendship quality (Biggs, Vernberg, & Wu, 2009), suggesting that facilitation of social engagement may be important in promoting the social adjustment of anxious youth and preventing comorbid depression. Interventions aimed at friendship facilitation are also promising, as having a good friend buffers against internalizing problems among victimized youth (Hodges, Boivin, Vitaro, & Bukowski, 1999), perhaps because talking to someone about aversive peer experiences can protect against loneliness (Vernberg, Ewell, Beery, & Freeman, 1995) and teacher-rated social problems (Kochenderfer-Ladd & Skinner, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It can lead youth to feel afraid of approaching peers, to avoid social interactions, or to experience significant distress while engaging in social interactions; not surprisingly, youth with higher social anxiety tend to experience less friendship support and peer acceptance (La Greca & Lopez, 1998). Youth with higher social anxiety are also more likely to withdraw socially, experience less companionship and intimacy from friends, and are more likely to refuse school (Biggs, Vernberg, & Wu, 2012; Nair et al, 2013). As social anxiety can undermine the formation of fulfilling friendships, adolescents may experience loneliness as a consequence.…”
Section: Introductionmentioning
confidence: 99%